Integrated Metabolomics and Network Pharmacology Study on the Mechanism of Rehmanniae radix Extract for Treating Thrombosis - Du H; Zhang S; Yuan K; Yang Z; Wu M (Dove Medical Press, 2024)
Hongling Du,1- 3 Shunjie Zhang,1 Kezhu Yuan,4 Zhirui Yang,5 Mingquan Wu4 1Department of Pharmacy, West China Hospital, Sichuan University, Chengdu, Sichuan, People's Republic of China; 2Department of Pharmacy, Sichuan Public Health Clinical Center, Chengdu, Sichuan, People's Republic of China; 3State Key Laboratory of Southwestern Chinese Medicine Resources, Pharmacy School, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, People's Republic of China; 4Department of Pharmacy, Sichuan Orthopedic Hospital, Chengdu, Sichuan, People's Republic of China; 5Department of Nuclear Medicine, Chengdu Second People's Hospital, Chengdu, Sichuan, People's Republic of ChinaCorrespondence: Mingquan Wu, Department of Pharmacy, Sichuan Orthopedic Hospital, Chengdu, Sichuan, People's Republic of China, Email 18782976939@163.comBackground: Rehmanniae Radix (RR) has received attention for its antithrombotic effect. However, few studies have independently explored the bioactive components responsible for its antithrombotic bioactivity and the potential mechanism. We aimed to reveal the antithrombotic mechanisms of RR by using metabolomics integrated with network pharmacology.Methods: A thrombosis model was established by intraperitoneal injection of type I carrageenan in rats, and antithrombotic function was evaluated at different doses of RR. Metabolomics was used to identify the differential metabolites in the serum. Network pharmacology was then applied to identify the potential targets for the antithrombotic activity of the RR. An integrated network of metabolomics and network pharmacology was constructed using Cytoscape. Finally, key targets were verified using molecular docking.Results: RR at 5.4 g/kg significantly alleviated the thrombosis. Thirteen potentially significant metabolites were involved in the therapeutic effects of RR against thrombosis, most of which were regulated for recovery after RR treatment. An integrated analysis of metabolomics and network pharmacology showed that the antithrombosis effect of RR was closely associated with the regulation of PLA2G2A, PTGS1, ALOX5, and CYP2C9. Molecular docking showed high affinity between the key targets and components of RR. We speculated that the components of RR, such as catalpol, ferulic acid methyl ester, and methyl 4-hydroxycinnamate, might act on key proteins, including PLA2G2A, PTGS1, and ALOX5, to exert antithrombosis effects.Conclusion: This study confirmed the antithrombotic effect of high-dose RR, revealed the antithrombotic mechanism and potential material basis, and laid the foundation for the antithrombotic clinical application of RR. Furthermore, it provides a successful case reference for screening natural herbal components and exploring their potential pharmacological mechanisms.Keywords: Rehmanniae radix, antithrombotic effects, metabolomics, network pharmacology